Field Insect Pests of Rohida (Tecomella undulata) in Arid Zones of Rajasthan - Verma, S K; Vir, Satya (Annals of Arid Zone, 2016)
Insects associated with Tceomella undulata in arid zones of Rajasthan have been listed and briefly discussed. Ptialus teeomello (Cioniindae, Curculioniodae: Coleoptera) and Stegmawphora sp. (Cosmopterygidae : Lepidoptera) are the key pests on established trees. whereas, Nadiosa siva (Lasiocampidae: Lepidoptera), Odolltotennes obesus (Termitidae: Isoptera) and Holorrichia consanguinca B1. ( Melolonthidae: Coleoptera ) are the key pests innurselY. Exorista sp. ( Tachinidae: Diptera ) is the major regulatory factor determining incidence and damage by Ptiolus tecomella.